ChemInform Abstract: A New Member of Ferrous Sulfates, FeSO4·2H2O with PtS Topology Showing Spin‐Canted Long‐Range Antiferromagnetic Ordering. Issue 50 (December 2015) - Zhao, Long; Liu, Wei; Cao, Lixin; Su, Ge; Gao, Rongjie; Yang, Hongzhan
Abstract: The title compound is solvothermally synthesized from a mixture of iron(III) citrate, 1, 6‐hexamethylenediamine, HF, H2 SO4, BuOH, and H2 O (autoclave, 423 K, 2 d), followed by addition of N2 H4 and HF to the reaction mixture (autoclave, 423 K, 5 d).